Laparoscopic resection of an intra-abdominal esophageal duplication cyst in the ileum: a case report - Shosaburo Oyama; Kenji Tanaka; Masaaki Moriyama; Takashi Nonaka; Tetsuro Tominaga; Terumitsu Sawai; Naoe Kinoshita; Takeshi Nagayasu (Surgical Case Reports, 2022)
Abstract Background Esophageal duplication cyst (EDC) is a type of gastrointestinal duplication cyst that involves congenital malformations of the gastrointestinal tract. EDCs are frequently found in the mediastinum and thoracoabdominal region, but rarely occur in the abdominal cavity. However, intra-abdominal EDCs are frequently found in the upper abdomen near the abdominal esophagus. Here, we report, for the first time, a case of intra-abdominal EDC that occurred in the ileum. Case presentation A 14-year-old female patient presented to our hospital with complaints of epigastric pain and vomiting. Abdominal computed tomography (CT) revealed a cystic tumor in the pelvis, suspected of ovarian origin. She was admitted to our gynecology department and underwent emergency surgery. The laparoscopic examination revealed that both ovaries were intact and that a primary tumor had developed from the ileal mesentery. Since the patient’s condition was not urgent at the time of the gynecological surgery, the procedure was completed by only performing exploratory laparotomy; the patient was admitted to our department after the surgery. Pelvic magnetic resonance imaging performed on the next day revealed a cystic mass measuring 90 × 65 mm with a smooth margin and homogeneous signal intensity, arising posterior to the uterus. The mass was suspected as an intestinal duplication cyst. On another day, after the examinations were completed, we resected the portion of the small intestine containing the tumor by laparoscopy. The patient had a successful postoperative course and was discharged on the 5th postoperative day. Histological examination showed that the cyst was lined by stratified squamous epithelium, contained esophageal glands, and had a two-layer muscularis propria. Therefore, a diagnosis of intra-abdominal EDC was performed. Conclusions An intra-abdominal EDC cyst is relatively rare; this is the first case reported at the distal ileum.